Decree No. 1081of the year 2017 concerning the definition of medium, small, and micro-projects / Egypt. Ministry of trade and industry ; translated by The middle east library for economic services. - Egypt. Ministry of trade and industry; The middle east library for economic services, translator. (2025)
Serial No. 45/2017